Pembelajaran Sejarah Melalui Pelatihan Kesenian Jathilan untuk Meningkatkan Pemahaman Terhadap Nilai-Nilai Lokal - Diana Trisnawati (Universitas Negeri Yogyakarta, 2017)
AbstractOne of the results of this study aims to clarify that the teaching of history has a lot of media or flexible in its delivery methods, such as through training Jathilan Art. Jathilan Art is one of the folk art using braid horse property, as well as players reog or lumping horse or horses braid. Art Jathilan Revelation turonggo in Kulon Progo Regency is one of folk art will be full of local values. Learning history through Art Jathilan training to improve local values are expected to provide new ideas in history. This is because history can not be separated from the cultures in a society. Meanwhile, art is one of the results of the culture. Teaching history at this point also raised many of the local values because Indonesia is a country rich in culture. To increase the love of the Indonesian state (nationalism) not only through pembelajarah history, especially the material history of the struggle of the Indonesian nation. How to boost nationalism can be done by increasing the understanding of local values. Local values can be instilled through training Art Jathilan include the values of mutual cooperation, kinship, the values of religious form of gratitude to God Almighty, the values of love for the surrounding environment, the values of self-reliance as using crops activities in the community, and so on. Keywords: Learning history, the traditional art “Jathilan”, local values